Macroprudential Frameworks in Asia - Barnett, Steven; Maino, Rodolfo (Washington, D.C. : International Monetary Fund, 2013)
This Departmental Paper portrays a cross-country dimension of macroprudential policy implementation in Asia, advancing a comprehensive overview of institutional arrangements and instruments deployed by individual countries to address systemic risk, including risk concentration and interconnectedness. This book is the first comprehensive collection of papers assessing the existing institutional arrangements for macroprudential policies in Asia.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet